Analisis Pembiayaan Akad Mudharabah Investor pada Navigasi Coffee and Roastery - Anteng Ayu Panularsih; Nanang Kurnianto (Jurnal Al-fatih Global Mulia, 2021)
Financing Analysis of Investor’s Mudharabah Contract in Navigasi Coffee and Roastery. Sharia Banking Study Program, STEBI Global Mulia Cikarang, 2020. Investor’s Mudharabah Contract financing in Navigasi Coffee and Roastery. The purpose of this research is to determine and analyze whether investor financing in Navigasi Coffee and Roastery is appropriate to the Sharia Law or not. The researcher studies how the management of Navigasi Coffee and Roastery manage funds received from the investor, so the business is able to run and develop. With that, the writer wants to analyze the financing of Investor’s Mudharabah Contract in Navigasi Coffee and Roastery. Based on that background, the writer has the following formulation of problem: 1) How Is the Investor’s Mudharabah Contract Financing Mechanism in Navigasi Coffee and Roastery? 2) How is the Implementation of Profit-Sharing System of Investor’s Mudharabah Contract in Navigasi Coffee and Roastery?. This research is a field research with qualitative approach. Data collection techniques through interviews and documentations. Data sources consists of primary data which is the result of field research that is interview with Navigasi Coffee and Roastery’s management, and secondary data which is research journal and financial statements of Navigasi Coffee and Roastery. Based on this research results can be said that Investor’s Mudharabah Contract Financing in Navigasi Coffee and Roastery is already in accordance with Sharia Law/Islamic Law. This is because Mudharabah’s condition has been met, namely: 1) There is “Ijab Qabul” or Binding Contract, 2) There are two parties, 3) There is capital, 4) The existence of business, 5) There are profits.